Comparative evaluation of apically extruded debris during root canal instrumentation using two Ni-Ti single file rotary systems: An in vitro study - Singbal, Kiran (J Conserv Dent, 2017)
BACKGROUND: Apical extrusion of debris during instrumentation is detrimental to the patient. AIM: The aim of this study was to evaluate the apical extrusion of debris during root canal instrumentation using two single file rotary Ni-Ti systems. MATERIALS AND METHODS: Thirty freshly extracted mandibular premolars with straight roots were sterilized and divided into two groups instrumented using: One Shape rotary Ni-Ti system with Endoflare orifice shaper (Group 1) and Neo-Niti rotary Ni-Ti system with C1 orifice shaper (Group 2). Preweighed Eppendorf tubes fitted for each tooth before instrumentation. During instrumentation, 1 mL of distilled water with a 30-gauge needle was used to irrigate after every instrument. Tips of the tooth were irrigated with 2 ml distilled water after removal from Eppendorf tubes. The total volume of irrigant in each group was the same 8 ml. All tubes were incubated at 68°C for 15 days and subsequently weighed. The difference between pre- and post-debris weights was calculated, and statistical analysis was performed using independent t-test and level of significance was set at 0.05. RESULTS: The difference between pre- and post-weights was significantly greater for the One Shape system. CONCLUSIONS: The Neolix Niti single file was associated with less extrusion compared to One Shape single file system.